Legal Protection Of Brand Rights And Geographical Indications For Toraja Coffee - Mutiara Nabila Rizqi; Upik Mutiara (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Geographical Indication is one of the Intellectual Property Rights that protects things that have features, attributes, or reputations related to the location from which they originated. Arabica coffee, which is native to Toraja South Sulawesi, has distinct attributes that distinguish it from other types of coffee, earning it a reputation as one of the world's best. The